Rejection of the Volost Zemstvo by the Multinational Population of Southeast Russia during the 1917 Election - Lyubichankovsky, Sergey (Quaestio Rossica, 2019)
This article contains an analysis of the election to the volost zemstvo in Southeast Russia in 1917. The study is based on documents from the archives of Stavropol, Astrakhan, and Orenburg regions, the State Archive of the Russian Federation, and materials from periodicals in the region under study. Soviet historiography claimed that the results of the 1917 election did not reflect the real (i. e. “left”) political preferences of the “masses”. However, the example of Southeast Russia does not support this conclusion. Party agitation did not play a decisive role in the zemstvo campaign. It would also be wrong to interpret the political predilections of the “underprivileged classes” as mainly Left Socialist-Revolutionary and Bolshevik. The failure of the election in national minority areas, the rather low voter turnout, and the election of relatively wealthy peasants as members of the city duma allow the author to conclude that in the 1917 election campaign, the traditional consciousness of the peasant population played a fundamental role. The traditionalism of Russian peasants was further strengthened due to the authorities’ special attitude towards their closest neighbours, i. e. representatives of national minorities. It was this traditionalism that impeded transition to a new management standard, i. e. the volost zemstvo, which was alien to peasants. The article demonstrates that the most important impediment for the reform was the mental conflict between advocates of the innovative “zemstvo volost” and adherents of traditionalist consciousness. The latter perceived the introduction of a volost zemstvo as an act of forced acculturation. It is concluded that the mental split of Russian society makes it possible to explain the pro-zemstvo orientation of many peasant councils of deputies and the anti-zemstvo attitude of both clan aristocracy and the majority of volost and rural chairmen. These factors explain the failure of the 1917 volost election in Southeast Russia in comparison to the centre of the country. It is noted that the cardinal conflict of opinions concerning the volost reform “from above” and “from below” predetermined the further development of the revolution in Southeast Russia.